HTTP blocking in CN: bbc.com, facebook.com, instagram.com, medium.com, nytimes.com +8 more (China) - Voidly (2026)
CRITICAL severity censorship detected in China. Confidence: 85%. Data sourced from CensoredPlanet.
Censorship Incident ID: CN-2026-0003
Keywords: censorship; CN; censorship; critical